Viabilitas Hepatosit pada Monokultur 3D Metode Hanging Drop dan Monokultur 2D - Sibuea, Christine Verawaty; Hutabarat, Enjelin Sasa Kristanti; Simangunsong, David M. T (Universitas HKBP Nommensen, 2022)
Background: Liver is a vital organ that has many functions including metabolism, detoxification of toxins and protein synthesis. The prevalence of liver disease is high and the treatment of liver disease continues to develop, so liver models are needed to study liver disease mechanisms and test drug toxicity. Many hepatocyte culture methods are being developed to construct an optimal liver model. The best culture method maintains high hepatocyte viability. Objective : This study aims to determine the viability of hepatocytes in 3D hanging drop method culture and in 2D culture. Methods: Hepatocytes were isolated from the liver of Sprague Dawley-Rats rats (n=2) and digested with Trypsin. Primary hepatocytes were cultured using the hanging drop method and conventional (2D) method. Hepatocyte viability was analyzed using the Trypan Blue Exclusion Test. Results: Hanging drop method had higher viability (81.18%) than the 2D culture method (69.22%) with p>0,05. Conclusion: The hanging drop method has better viability than the 2D culture method. Keywords: Hepatocyte, viability, 3D culture, 2D culture, hanging drop Latar belakang: Hati merupakan organ vital tubuh yang memiliki banyak fungsi diantaranya metabolisme, detoksifikasi racun dan sintesis protein. Prevalensi penyakit hati tinggi dan terapi penyakit hati terus berkembang, sehingga model hati sangat dibutuhkan untuk mempelahari mekanisme penyakit hati dan uji toksisitas obat. Banyak metode kultur hepatosit yang terus dikembangkan untuk menghasilkan suatu model hati yang optimal. Metode kultur yang terbaik adalah metode kultur dengan viabilitas hepatosit yang tinggi. Tujuan : Penelitian ini bertujuan untuk mengetahui viabilitas hepatosit pada kultur 3D metode hanging drop dan pada kultur 2D. Metode: Hepatosit diisolasi dari hati tikus Sprague Dawley-Rats (n=2) dan digesti dengan Tripsin. Hepatosit primer tikus dikultur dengan metode hanging drop (tetes gantung) dan metode konvensional (2D). Viabilitas hepatosit dianalisa dengan menggunakan Trypan Blue Exclusion Test. Hasil: Viabilitas hepatosit pada metode hanging drop memiliki viabilitas lebih tinggi (81,18%) dibandingan dengan metode kultur 2D (69,22%) dengan nilai p<5. Kesimpulan: Metode hanging drop memiliki viabilitas yang lebih baik dibandingkan metode kultur 2D. Kata Kunci: Hepatosit, viabilitas, kultur 3D, kultur 2D, hanging drop